Between Academic Resilience and Burnout: The Moderating Role of Satisfaction on School Context Relationships - Luciano Romano; Piermarco Consiglio; Giacomo Angelini; Caterina Fiorilli (MDPI AG, 2021)
School burnout is considered an extreme form of maladjustment that can seriously undermine the academic path of students who are affected. Previous studies have focused on possible protective factors, highlighting the role of academic resilience, i.e., the ability to overcome chronic adversity in the school setting. Notwithstanding this, it is equally important to explore the role of the classroom environment and the satisfaction felt by the student toward relationships with teachers and classmates. Therefore, the purpose of the present study was to examine the relationship between academic resilience and burnout and to explore the moderating role of relationship satisfaction with teachers and classmates. A sample of 576 Italian students (Female = 53.1%), aged 14-18 (M = 15.73, SD = 1.56) were involved in the study. Correlations and moderated regressions analyses were conducted to test the hypotheses. The results show academic resilience and satisfaction as inversely related to school burnout. Furthermore, the satisfaction on the relationships with classmates moderated the relation between academic resilience and burnout. Findings were discussed by highlighting the importance of promoting both individual and contextual factors to prevent burnout risk.